The role of entrepreneurial management in achieving a proactive sustainability strategy A case study in Al-Zawraa State Company and the Electrical and Electronic Industries - dawood, Fadheelah salman; Al-Badri , Basma Ayad Kazem (The journal of contemporary issues in business and government, 2021)
The research aims to know the role that the entrepreneurial management plays in achieving a proactive sustainability strategy in Al-Zawraa State Company and the Electrical and Electronic Industries Company. Accelerated. The research problem was formulated with the following question: Can the entrepreneurial management achieve a proactive sustainability strategy and the possibility of its application in the General Company of Al-Zawra and the Electrical and Electronic Industries Company of the Ministry of Industry and Minerals operating in Iraq, and the selection of the research sample from the senior leaders of the Al-Zawra General Company to collect information to extract results from the checklist to determine The gap and its treatment for the two companies researched. The research yielded a set of results, the most important of which are: weakness in implementing proactive strategies capable of overcoming difficulties, especially for the Electrical and Electronic Industries Company, in the field of strategic orientation, as well as the existence of a large gap in the dimension of the social and environmental performance of the two companies to varying degrees.